Industrial-organizational psychology - Miner, John B. (McGraw-Hill, 1992)
This is a text for the industrial organizational psychology course which covers the organizational material first and then the personal material. The author's varied experience in this field enables him to draw from personal case studies and introduce research, issues, designs and results throughout the organizational course in psychology, business and management departments. This is the reverse order of the traditional texts. Current teaching trends suggest the need for this reversal in coverage, remaining balanced.